2017
DOI: 10.1021/acs.iecr.7b02854
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Carbon from Sodium Lignosulfonate by Hydrothermal and Template Method and Its Adsorption of Uranium(VI)

Abstract: A novel adsorbent of mesoporous carbon with high specific surface area was successfully prepared by hydrothermal and template method, using sodium lignosulfonate (LSs) as a raw material and cetyltrimethylammonium bromide (CTAB) as a template agent. The mesoporous carbon was characterized by SEM, TEM, BET, FTIR, and XPS. The formation mechanism of the mesoporous carbon was analyzed. The adsorption of uranium(VI) on the mesoporous carbon from the simulated aqueous solution and actual radioactive wastewater was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Moreover, the comparison of fitted coefficients ( R 2 ) from two models indicated that the adsorption kinetics could be better described by pseudo-second-order model (0.9993 and 0.9998) than that of pseudo-first-order model (0.8044 and 0.7253). Based on the assumption of pseudo-second-order model, the adsorption mechanism was chemisorption process between CFL and metal ions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the comparison of fitted coefficients ( R 2 ) from two models indicated that the adsorption kinetics could be better described by pseudo-second-order model (0.9993 and 0.9998) than that of pseudo-first-order model (0.8044 and 0.7253). Based on the assumption of pseudo-second-order model, the adsorption mechanism was chemisorption process between CFL and metal ions …”
Section: Resultsmentioning
confidence: 99%
“…Based on the assumption of pseudo-second-order model, the adsorption mechanism was chemisorption process between CFL and metal ions. 32 To evaluate the adsorption capacity, the adsorption isotherms were examined with various concentrations in the range of 25−500 mg/L of metal ions at 15 °C. In Figure 2d, the adsorption capacities of Cu(II) and Pb(II) by CFL increased with increases in metal ion concentrations and finally leveled off at 68.7 and 55.5 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…57 These hydrated species are more easily adsorbed due to their high affinity for solid surfaces. 58 Kinetic study. The results of adsorption experiments in dependent of the contact time for BSG and ABSG are depicted in Fig.…”
Section: +mentioning
confidence: 99%
“…In particular, uranium presents renal, developmental, and reproductive toxicity and causes diminished bone growth and DNA damage, as obtained from experimental animal studies and human epidemiology. 5 Numerous adsorbents have been explored to remove uranium from the water environment, such as mesoporous carbon, 6 graphene oxides, 7 hydrochar, 8 chitosan, 9 amidoxime-based materials, 10 and functional fibrous material-based adsorbents. 11 Natural organic raw materials are the most attractive materials for green adsorbent production, and the diversity of raw materials of biosorbents has been increased rapidly, including hazelnut shells, 12 chitosan, 13 nanocellulose, 14 starch, 15 saw dust, 16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…where k F ((mg/g) (L/mg) 1/n ) is the Freundlich isotherm constant related to adsorption capacity and n is the Freundlich isotherm constant related to adsorption intensity (6) where k R (L/g) and a R (L β /mg β ) are the Redlich−Peterson isotherm constants and β is the Redlich−Peterson isotherm exponent. The fitting results and isotherm parameters are summarized in Table 2, and the detailed statistical evaluations are given in Table S8.…”
mentioning
confidence: 99%